STRATEGI PENGEMBANGAN HOME INDUSTRY TENUN IKAT DENGAN MEMPERHATIKAN RAMAH LINGKUNGAN DI DESA LAMAPAHA KECAMATAN KELUBAGOLIT KABUPATEN FLORES TIMUR - Kewa, Susanti; Wulakada, Hamza Huri; Hasan, Muhammad Husain (Universitas Nusa Cendana, 2022)
The aims of this study are (1) to determine the types of problems in the ikat weaving industry in Lamapaha Village, (2) to identify the threat of environmental damage and pollution from the ikat weaving production process in Lamapaha Village, (3) to determine what factors hinder and support the sustainability of the ikat weaving industry. Ikat home industry in Lamapaha Village (4) to find out how the strategy is to overcome the problems of developing ikat home industry in Lamapaha Village. This research method is descriptive qualitative. The respondents in this study were ikat craftsmen in Lamapaha Village. Data analysis used in this research is descriptive qualitative and SWOT analysis. The results of this study are (1) ikat weaving is a culture whose benefits are enhanced and can then be referred to as a side business. But based on the characteristics of the weaving activity, ikat weaving can be classified as a home industry activity. (2) Home industry activities pose a threat to pollution and environmental damage, namely the felling of trees in the manufacture of tools and materials that produce chemical waste in the process of making ikat and waste that can damage the surrounding environment (3) Supporting factors are: as a culturally inherited from generation to generation, natural resources are easy to obtain, add to the family's economy, good quality, take advantage of free time. inhibiting factors: self-consumption, use of chemicals, soil pollution and damage to the surrounding ecosystem, the workforce is generally old. (4) The strategy of developing a home industry for ikat weaving by taking into account environmental friendliness in Lamapaha Village is to develop cooperation, increase socialization about environmental pollution and empower weaving groups.